2018
DOI: 10.3389/fmicb.2018.01906
|View full text |Cite
|
Sign up to set email alerts
|

Human Campylobacteriosis in Italy: Emergence of Multi-Drug Resistance to Ciprofloxacin, Tetracycline, and Erythromycin

Abstract: Campylobacter spp. is one of the main cause of bacterial gastroenteritis in the world. The increase of antibiotic resistance in this species is a threat to public health. A Campylobacter spp. surveillance study was performed in Italy in the 2013–2016 period by the Enter-Net Italia network. The most prevalent Campylobacter species identified causing gastroenteritis was Campylobacter jejuni (73.4%) and 45% of all the annual cases of campylobacteriosis were reported in the summer period. High rates of ciprofloxac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 41 publications
5
38
1
Order By: Relevance
“…Moreover, C. coli was also the most frequent isolate (5%) in patients with asymptomatic PAD, followed by C. jejuni (1.2%), whereas in immunocompetent individuals, C. jejuni is one of the most prevalent etiologic agents of gastroenteritis and C. coli has a low prevalence in diarrheal disease. 3,4 Differently from the French data, we showed that the same C. coli strain has been isolated for more than 10 years in an asymptomatic patient with XLA. 2 As previously shown, 5 after this long-lasting silent infection, the same intestinal strain caused recurrent episodes of sepsis and leg cellulitis, without changing its molecular pattern.…”
contrasting
confidence: 56%
“…Moreover, C. coli was also the most frequent isolate (5%) in patients with asymptomatic PAD, followed by C. jejuni (1.2%), whereas in immunocompetent individuals, C. jejuni is one of the most prevalent etiologic agents of gastroenteritis and C. coli has a low prevalence in diarrheal disease. 3,4 Differently from the French data, we showed that the same C. coli strain has been isolated for more than 10 years in an asymptomatic patient with XLA. 2 As previously shown, 5 after this long-lasting silent infection, the same intestinal strain caused recurrent episodes of sepsis and leg cellulitis, without changing its molecular pattern.…”
contrasting
confidence: 56%
“…In our study, we noted the presence of the tet (O) gene in 88.88% of isolated pigs, indicating a very strong correlation (98.76%) between phenotypic and genotypic resistances, which decrease to the 80% level of concordance in humans. The high resistance to tetracycline of bacteria isolated from food, including Campylobacter, remains a serious problem in many European countries [40]. Fluoroquinolone resistance in our strains was mainly due to the presence of the Thr86Ile GyrA mutation.…”
Section: Discussionmentioning
confidence: 70%
“…High levels of resistance to ciprofloxacin (52.3%) and tetracyclines (51.5%) were also observed in C. coli from fattening pigs, with a lower percentage for erythromycin (15.6%). Combined resistance to ciprofloxacin and erythromycin was reported in 61.2% of C. coli isolates from fattening pigs in Spain [40]. In Italy, high rates of ciprofloxacin and tetracycline resistance in Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45][46] The resistance to fluoroquinolones is especially a concern as in many countries, the majority of Campylobacter isolates are no longer susceptible to this class of antibiotics. 18,[47][48][49][50] In the U.S., a recent CDC report revealed a rising trend of ciprofloxacin-resistant Campylobacter for the past two decades and the resistance rate reached 29% in 2017. 9 A unique feature of fluoroquinolone resistance in Campylobacter is its continued persistence or even increased prevalence in the absence of antibiotic usage.…”
Section: Antibiotic Resistance and Alternative Antibiotic Therapymentioning
confidence: 99%